HUBUNGAN MINAT MEMBATIK DENGAN PRESTASI BELAJAR BATIK SISWA SEKOLAH MENENGAH KEJURUAN - Tin Dels Marce Ndawu (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2017)
The purpose of this study to determine (1) batik work interest (2) batik learning achievement (3) batik interest relationship with the batik  learning achievementsof tenth grades student in Yogyakarta 5 vocational high school. The study of population was tenth grade who were sixty-onestudents. Instrument in this study was a questionnaire and documentation. This study used a sampling technique that was developed by Isaac and Michael. Data analysis technique used descriptive analysis technique and correlational analysis with the analysis that  preceded requirement normality test, linearity. Hypothesis testing used product moment correlation analysis.The result of this study indicated that interest in batik category quite 63,9% and batik learning achievements category quite 47,5%. The value of r bigger than r table of r ( 0,445 ≥ 0,244 ). The given amount of donations can be seen from the determinant coefficient value by 0,198. It  showed  the amount of donations by batik interest to batik learning achievement by 19,8%, the restby 80,2% of the donations came from social intercourse, family environment and neighborhood. Thus batik working interest could affect student batik learning achievements. Keywords : Batik Working Interest, Batik Learning Achievement